Leg myxoid liposarcoma: correlation between image and anatomopathological tests - Marcio Luís Duarte; Élcio Roberto Duarte; Edgard B. Solórzano; Jael B. A. Ferreira (Sociedade Brasileira de Patologia Clínica, 2020)
ABSTRACT A 41-year-old male patient refers to a painful tumor on the lateral side of the right leg. Ultrasonography visualized a predominantly hypoechoic well-delineated large heterogeneous mass in the subcutaneous tissue, showing an internal hyperechoic area. Magnetic resonance imaging (MRI) demonstrated an oval and lobulated tumor with well-defined margins at the anterolateral part of the leg, with contrast enhancement. The anatomopathological evaluation revealed a neoplasm with an extensive chondromyxoid matrix. The immunohistochemical study demonstrated positive vimentin (V9 clone), positive S-100 protein and negative desmin (D33 clone), smooth muscle actin (1A4), CD68 (KP1 clone) and caldesmon. The set of findings is compatible with myxoid liposarcoma.